2001
DOI: 10.1002/jcb.10015
|View full text |Cite
|
Sign up to set email alerts
|

Differential maintenance and de novo methylating activity by three DNA methyltransferases in aging and immortalized fibroblasts

Abstract: Genomic methylation, which influences many cellular processes such as gene expression and chromatin organization, generally declines with cellular senescence although some genes undergo paradoxical hypermethylation during cellular aging and immortalization. To explore potential mechanisms for this process, we analyzed the methylating activity of three DNA methyltransferases (Dnmts) in aging and immortalized WI-38 fibroblasts. Overall maintenance methylating activity by the Dnmts greatly decreased during cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(103 citation statements)
references
References 54 publications
4
97
2
Order By: Relevance
“…The potential mechanism of age-related demethylation of a single locus is not clear; the cellular activity of DNA methyltranserase 1 decreases with age but this is likely to lead to a global loss in methylation which we did not observe [33]. Another potential mechanism is related to the effects of chronic age-related low grade inflammation leading to the production of reactive oxidative molecules with resultant conversion of 5-methylcytosine to 5-hydroxymethylcytosine [34].…”
Section: Discussionmentioning
confidence: 74%
“…The potential mechanism of age-related demethylation of a single locus is not clear; the cellular activity of DNA methyltranserase 1 decreases with age but this is likely to lead to a global loss in methylation which we did not observe [33]. Another potential mechanism is related to the effects of chronic age-related low grade inflammation leading to the production of reactive oxidative molecules with resultant conversion of 5-methylcytosine to 5-hydroxymethylcytosine [34].…”
Section: Discussionmentioning
confidence: 74%
“…A recently published longitudinal study of 718 elderly individuals between 55 and 92 years of age demonstrated that repetitive element methylation, particularly in Alu sequences, decreases throughout aging (31). It has been postulated that the reduction of Dnmt1 activity, the predominant maintenance DNA methyltransferase, with age contributes to the decrease in global DNA methylation (32,33). However, although genome-wide levels of methylation decrease with age in mammals, methylation levels can be either increased, decreased or unchanged depending on the specific strain of mice, tissue or gene examined (recently reviewed in (34)).…”
Section: Epigenetic Changes In Agingmentioning
confidence: 99%
“…However, aging-associated increases in the methylation of some genes are also reported (Issa et al, 1994;Issa et al, 1996;Wallace et al, 2010). Generally, ODC (Minois et al, 2011) and Dnmt (Lopatina et al, 2002;Oliveira et al, 2012;Romanenko et al, 1998) et al, 2004;Li et al, 2010;Morgan et al, 2005). Because there is a close relationship between Dnmt activities and the methylation status of LFA-1 promoter regions, and since aging is associated with decreased Dnmt activities as well as increased demethylation of the LFA-1 promoter region (Zhang et al, 2002), the agingassociated enhancement of LFA-1 expression seems to be due to the age-dependent decreases in Dnmt activities.…”
Section: Aging and Gene Methylationmentioning
confidence: 98%